PEMAHAMAN HADIS RU’YATAL-HILAL MENURUT ULAMA SYATARIAH ULAKAN PADANG PARIAMAN - Nandi Pinto (Jurnal Ulunnuha, 2017)
The Problem of hisab and ru’yat on its development are not regardless of development Islamic thingking history who much be embellishment of ideology, mazhab or firqah, who present differentiation on opinion who related Islamic law framework especially in Indonesia. The result of understanding different about argumentation normative hisab-ru’yat were think out a differntiation and understanding on the Islamic member of a religious community. This thesis is field research, who has special understanding on construe of Hadis ru’yat al-hilal of Tarekat Syatariah. Interpretation this Hadith of Tarekat Syatariah have different understanding to understand the context of Hadis. Now focus of this research is to know understanding and implementation of Hadith ru’yat al-hilal according to Syatariah scholar Ulakan Padang Pariaman. The result of this research are, First, understanding of hadis ru’yat al-hilal according to Syatariah scolar Ulakan Padang Pariaman is both collaboration of that hadis, because of the first hadis be explanation of the second hadis that are when the moon can’t be seen with the naked eyes because closed of fog or cloud, than word of presuppositioning (faqdurulah) on the first hadis be exclamation of passages of Koran by supplying additional information by Syatariah scholar be completed Sya’ban moon to be 30 days. Second, understanding implementation of Hadis ru’yat al-hilal is with together see new moon (al-hilal) at place who be certained of scolar (Tuangku) from the last time , they are Ulakan beach Padang Pariaman and Koto Tuo Agam. They are see new moon naked eye, although use the modern tools to see it the last judgmen according to them how to see it with naked eye, if it can’t be seen so, the new moon was not visible, although with modern tools to see it, and that not have influenced on determination al-hilal was seem or not. Their jedgment is still on argument if the new moon can’t see with naked eyes, so, al-hilal be evidented not visible and Sya’ban moon be completed to 30 days.